Analisis Penggunaan Bahasa Indonesia dalam Komunikasi Pemain Online Game: Studi Pengaruh Sosial - Anhar, Anhar; Donita W, Eva Celia; Muliadi, Felicia; Valent, Jill; Hamidah, Zellica Gani (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Online games have become a popular communication space for various age groups, forming unique patterns of language interaction among players. This study aims to analyse the use of Indonesian in online game player communication and examine the social influences that arise from such language practices. The research uses a qualitative descriptive method by observing player conversations, analysing the content of communication in the game, and reviewing the forms of language use that emerge, such as slang, abbreviations, code-mixing, and emotional expressions. The results show that players tend to use non-standard language, including slang and abbreviations, which affect the accuracy of Indonesian language usage. In addition, the use of foul language was also found to have a negative impact on the dynamics of interaction and communication culture in the gamer community. These findings indicate that language practices in online games not only reflect group identity but also influence the formation of attitudes and social relationships among players.